The toxic triangle in academia: A case analysis of the emergence and manifestation of toxicity in a public university. (August 2019) - Pelletier, Kathie L; Kottke, Janet L; Sirotnik, Barbara W
In this case analysis, we apply the toxic triangle framework, in its entirety, to a public university upon the entry of a new president. We found considerable fit of the theoretical triad to the university: a destructive leader, an enabling environment, and susceptible followers. Consistent with the theory, an environment that lacked fundamental checks and balances, coupled with instability and perceived threats, spawned the conditions that brought a toxic leader to the institution, which, in turn, revealed and fostered conformers and colluders. We describe three episodes (critical incidents) that show how the toxic triangle evolved and strengthened over time. We also offer a critical examination of all three components of the toxic triangle with a special focus on the psychosocial forces that paralyzed even tenured faculty from resisting. In this critical examination, organizational miasma, rationalizations, and control myths provide substantive explanations for ineffective employee action. Further, we suggest that leadership as processual communication can be used to advance the value of the framework. We conclude by highlighting areas for future inquiry.